2016
DOI: 10.1007/s13197-016-2400-z
|View full text |Cite
|
Sign up to set email alerts
|

Studies on physico-chemical and cooking characteristics of rice bean varieties grown in NE region of India

Abstract: Rice bean () is grown in South and Southeast Asia, and the bean has gained importance due to its nutritional strength in terms of dietary fiber, quality protein and minerals. In current study, the nutritional and functional components, cooking and thermo-gravimetric properties of eleven rice bean varieties from NE India were investigated. Results revealed that the major nutrients among the varieties ranged as follows: 54.21-60.49% carbohydrates, 15.64-21.60% protein, 1.22-2.3% fat, 5.53-6.56% crude fibre, 3.34… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 28 publications
(33 reference statements)
1
20
0
Order By: Relevance
“…Rice bean is considered as a low-fat food. The range of saturated and unsaturated fats varied considerably in the reported studies (Kaur and Kapoor 1992;Saikia et al 1999;Katoch 2013;Bepary et al 2017). Crude fat content varied from 0.46 to 2.3%.…”
Section: Nutritional Compositionmentioning
confidence: 95%
See 3 more Smart Citations
“…Rice bean is considered as a low-fat food. The range of saturated and unsaturated fats varied considerably in the reported studies (Kaur and Kapoor 1992;Saikia et al 1999;Katoch 2013;Bepary et al 2017). Crude fat content varied from 0.46 to 2.3%.…”
Section: Nutritional Compositionmentioning
confidence: 95%
“…Katoch (2013) analysed 16 genotypes of rice bean and reported 15.33-28.23 mg (per 100 g) ascorbic acid and 3.48-4.26 mg (per 100 g) niacin. Kaur and Kapoor (1992), Mohan and Janardhanan (1994), Katoch (2013) and Bepary et al (2017) studied mineral content in rice bean grain. From these studies, it can be concluded that rice bean is rich in sodium (Na), potassium (K), calcium (Ca) and phosphorous (P).…”
Section: Nutritional Compositionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ricebean is an underutilised minor bean of India which is mainly available in South and South-Eastern Asian countries and to a limited extent in West Indies, USA, Queensland (Australia) and in East Africa 13 . In North-East India, it is conventionally used to prepare curry and deep fried snacks.…”
Section: Introductionmentioning
confidence: 99%